TEXTUAL METAFUNCTION ANALYSIS ABOUT EDUCATION NEWS TEXT ON SELECTED NATIONAL ONLINE NEWSPAPERS - Shela Noviriantika Hidayah; Marwito Wihadi; Wulan Rahmatunisa (UIBU, 2023)
The textual meta function is about the verbal world, especially the flow of information in a text, and is concerned with clauses as messages. In each meta function an analysis of a clause gives a different kind of structure composed from a different set of elements. The aim of this study was to analyze and identify the functions took from three different online newspapers, Jakarta Post, Jakarta Globe, and Tempo, with the context of educational news on the topic,